Direct Inhibition by Nitric Oxide of the Transcriptional Ferric Uptake Regulation Protein via Nitrosylation of the Iron - D'Autréaux, Benoît; Touati, Danièle; Bersch, Beate; Latour, Jean-Marc; Michaud-Soret, Isabelle (Proceedings of the National Academy of Sciences - PNAS, 2002)
Ferric uptake regulation protein (Fur) is a bacterial global regulator that uses iron as a cofactor to bind to specific DNA sequences. The function of Fur is not limited to iron homeostasis. A wide variety of genes involved in various mechanisms such as oxidative and acid stresses are under Fur control. Flavohemoglobin (Hmp) is an NO-detoxifying enzyme induced by NO and nitrosothiol compounds. Fur recently was found to regulate hmp in Salmonella typhimurium, and in Escherichia coli, the iron-chelating agent 2,2′-dipyridyl induces hmp expression. We now establish direct inhibition of E. coli Fur activity by NO. By using chromosomal Fur-regulated lacZ reporter fusion in E. coli, Fur activity is switched off by NO at micromolar concentration. In vitro Fur DNA-binding activity, as measured by protection of restriction site in aerobactin promoter, is directly sensitive to NO. NO reacts with FeIIin purified FeFur protein to form a S = 1/2 low-spin FeFur-NO complex with a g = 2.03 EPR signal. Appearance of the same EPR signal in NO-treated cells links nitrosylation of the iron with Fur inhibition. The nitrosylated Fur protein is still a dimer and is stable in anaerobiosis but slowly decays in air. This inhibition probably arises from a conformational switch, leading to an inactive dimeric protein. These data establish a link between control of iron metabolism and the response to NO effects.